CARDIOVASCULAR DISEASE AMONG ADOLESCENCE IN SMPN 5 MALANG: A CROSS-SECTIONAL SURVEY STUDY - Cholid Tri Tjahjono; Fandy Hazzi Alfata; Heny Martini; Indra Prasetya; sawitri satwikajati (Universitas Brawijaya, 2021)
Cardiovascular disease (CVD) is the leading cause of death in Asia-Pacific, although highly preventable, CVD was the cause of an estimated 9.4 million deaths. It accounted for one-third of all deaths in 2016. Hypertension is one of cardiovascular disease risk factors. Early detection of cardiovascular disease is the main issues to reduce the prevalence of the cardiovascular disease. Adolescence was the population in which the modifiable cardiovascular risk factor firstly developed. In the year 2018, Indonesian Health Ministry discovered that the prevalence of the cardiovascular disease in East Java was 0.2 % higher than national prevalence and Malang as one of the biggest cities in East Java with high population growth, hence early detection of cardiovascular disease become highlight issue. This cross-sectional survey was held in September 2019 at SMPN 5 Malang, which participated by 123 students (75 females and 48 males). Bivariate analysis was done to examine the correlation between each variable, and logistic regression was done to the most influential variable. Seventy-eight per cent of students were sedentary lifestyle with physical activities < 300 minutes/week, 16.2 % of students were an active smoker, and all were male. Among 123 students, 0.8 % with no cardiovascular risk factor, 29.2 % had 1 risk factor, 30.8 % had 2 risk factors, 27.6 % had 3 risk factors, and 11.3 % had 4 risk factors. The most prevalent risk factors were sedentary life (80 %), increase waist circumference (50 %), passive smokerÂ (48.5 %), overweight & obesity (15 %), and active smoker (14,6 %). Waist circumference above normal was more prevalent in female (65 %) than male (31%). Hypertension had been found in 14.6 % of students and had a significant correlation with heart rate (p 0.011)